Unplanned Extubation and Subsequent Trial of Noninvasive Ventilation in the Neonatal Intensive Care Unit - Nesbitt, Gemma; Guy, Katelyn J.; König, Kai (American Journal of Perinatology, 2015)
Objective Unplanned extubation (UE) occurs as an infrequent complication of mechanical ventilation in the neonatal intensive care unit (NICU). Following UE, a trial of noninvasive ventilation (NIV) may be considered if a neonate is showing adequate respiratory effort. This study investigated the success and failure rate of NIV management of neonates experiencing UE.Study Design Retrospective single-center study of neonates experiencing UE in the NICU over a 9-year period. Reintubation within 12 hours of a trial of NIV following UE was defined as treatment failure. Short-term respiratory outcomes were analyzed for all infants plus the incidence of bronchopulmonary dysplasia for preterm infants born less than 32 weeks' gestation.Results A total of 43 patients were included. Of those, 30 infants were trialed on NIV following UE. Baseline demographics were similar between both the groups except for the oxygen requirement before UE. The NIV was successful in 20 and failed in 10 infants. Infants who failed a trial of the NIV were reintubated between 0.45 and 5.25 hours following UE. Respiratory outcomes in very preterm infants did not differ between groups.Conclusion A trial of NIV may be considered as a treatment option in preterm and term newborns experiencing UE in the NICU.
Keywords: preterm infants; newborn; extubation; noninvasive ventilation; continuous positive airway pressure